Green biosynthesis of rare DHA-phospholipids by lipase-catalyzed transesterification with edible algal oil in solvent-free system and catalytic mechanism study - Zhang, Tiantian; Li, Binglin; Wang, Zhulin; Hu, Dan; Zhang, Xiaoli; Zhao, Binxia; Wang, Jiao (Frontiers in Bioengineering and Biotechnology, 2023)
Docosahexaenoic acid (DHA)-enriched phosphatidylcholine (PC) has received significant scientific attention due to the health benefits in food and pharmaceutical products. In this work, the edible algal oil without pretreatment was first used as the DHA donor for the transesterification of phospholipids (PLs) to prepare three kinds of rare PLs, including DHA-PC, DHA-phosphatidylethanolamine (DHA-PE), and DHA-phosphatidylserine (DHA-PS). 153 protein structures of triacylglycerol lipase (EC 3.1.1.3) were virtually screened and evaluated by transesterification. PLA1 was the best candidate due to a higher DHA incorporation. Results showed that the transesterification of PC with DHA-TAG at 45°C and 0.7% water content (without additional water addition) could produce DHA-PC with 39.1% DHA incorporation at 30 min. The different DHA donors, including forms of fatty acid, methyl ester, and triglycerides, were compared. Molecular dynamics (MD) was used to illustrate the catalytic mechanism at the molecular level containing the diffusions of substrates, the structure-activity relationship of PLA1, and the effect of water content.